THE IMPACT OF SOCIAL INFLUENCE FACTORS IN ACCEPTANCE RATE OF VALORANT GAME - Herdiansyah, Firman; Napitupulu, Togar Alam (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
VALORANT is an online team-based first-person shooter game developed by Riot Games. Currently VALORANT is popular among gamers because the game is similar to the Counter Strike but is given a skill set like the Overwatch. Now players on Indonesia are 560k player which so big and interesting to know the factors of this phenomenon. This study aims to determine the factors of social influence impacted the acceptance rate. The research model used in this study is TAM which is then modified as needed by using 6 constructs, namely Perceived Usefulness, Perceived Ease of Use, Social Influence, Attitude Toward Use, Intention to Use and Actual Usage as representatives of acceptance. The method of data collection in this study was to distribute surveys to 105 respondents in Jakarta. The results show that all variables affect Actual Usage except Perceived Ease of Use, although most respondents feel that this game is easy to understand. The results that have been discussed can be used as empirical recommendations to developers who want to make similar games.